Analysing the Spatial structure of the Street network to understand the Mobility pattern and Landuse - A case of an Indian city - Mysore - Pappu, Harcharan (TeMA - Journal of Land Use, Mobility and Environment, 2018)
Settlements grow and develop their unique spatial structure, subject to the factors influencing them. Later, the spatial structure starts influencing the functions of a settlement, like mobility, land-use, spatial expansion, etc. To understand the dynamics of the spatial structure and its influence in a rational way, a scientific analysis is necessary. So, space syntax measures are chosen as the principal theoretical postulates for analysis, because of its quantitative and scientific approach. In this paper, an attempt has been made to analyse the spatial structure of the street network in an Indian city – Mysore – by a comprehensive application of space syntax techniques. The study has been conducted by breaking down the structure into components and by analysing the use of different measures, like integration and choice, using Depthmap software (Turner, 2012). The analysis is then related to the existing mobility pattern and land-use to construe how the spatial structure influences the mobility pattern and land-use.